If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = y + -10 Reorder the terms: 5 = -10 + y Solving 5 = -10 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 5 + -1y = -10 + y + -1y Combine like terms: y + -1y = 0 5 + -1y = -10 + 0 5 + -1y = -10 Add '-5' to each side of the equation. 5 + -5 + -1y = -10 + -5 Combine like terms: 5 + -5 = 0 0 + -1y = -10 + -5 -1y = -10 + -5 Combine like terms: -10 + -5 = -15 -1y = -15 Divide each side by '-1'. y = 15 Simplifying y = 15
| 7z-9=-9 | | 5+1/4y=6 | | 5x^2-17+6=0 | | 1/4y=10 | | (5x^2+2x-3)-(7x^3-4x^2+2)= | | 5n-10=n+50 | | 16x^3y-54y= | | x^2-24x+144+256=x^2 | | 5y-15x=45 | | 14x+55=11x+94 | | 7x-4(x-3)=33 | | t/250=150/375 | | 1/4(2x+5)=x-2/5 | | =(7x+9y-2x)(8x-3x-3y) | | 7x+1=2x+6 | | 1/2+(0.7)2 | | (3x+2)=(x-7) | | -9x+63=135 | | (m^-1m5/m^-2)^-3 | | -1/12x+8=7/6 | | x/0.02=32.8 | | -3x=18.9 | | 4c-6=250 | | 47y+5x=360 | | 3x-10=12x | | x(3x^2+5x-4)-3(3x^2-x)=0 | | X*X-3=-2 | | 7(r+3)= | | 2x+7y=28 | | 8p+4-8p= | | x*.06=3500 | | 6x-73+8x+43=180 |